Vinyl‐/Furoindoles and Gold Catalysis: New Achievements and Future Perspectives for the Synthesis of Complex Indole Derivatives - Pirovano, Valentina; Abbiati, Giorgio; Brambilla, Elisa; Rossi, Elisabetta (European journal of inorganic chemistry, 2020)
The reactivity of vinyl‐/furoindole derivatives with gold‐activated π‐systems is the subject of extensive investigation. In the presence of these electrophilic partners, the realized transformations allow for the construction of different and fascinating architectures via cycloaddition and cyclization reactions often included in cascade processes. The reactions realized involving in these processes an external substituent at the indole moiety are the subject of the present minireview. The use of substituted or polycyclic indoles in reactions with gold‐activated π‐systems allows for the synthesis of new classes of carbazole derivatives and highly functionalized indoles under mild conditions and with high level of regio diastereo and enantio selectivities.